1981
DOI: 10.1038/bjc.1981.278
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of adriamycin and mAMSA in vitro: Cell lethality and SCE studies

Abstract: Summary.-We have compared the actions of ADM and mAMSA in Chinese hamster V79 cells in vitro, using cell survival and sister-chromatid exchange as end-points.Equimolar concentrations of ADM and mAMSA show similar toxicities to exponentially growing cells, and both drugs are less effective in killing chronically hypoxic and plateau-phase cells. Cytotoxicity to thermotolerant cells (41°C for 16 h previously) shows little difference from that for exponential cells. Pre-treating cells with misonidazole under hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Our results are also consistent with observations made by West et al (1981) to 0.2 gM of m-AMSA for 1 hr, demonstrated distribution patterns with a large variance, similar to the ones we observed at 1 #M m-AMSA. In similar studies, Kao-Shan et al (1984) studied cytogenetic effects of m-AMSA in human lymphocytes, observing potent SCE induction with doses ranging from 0.005 #g/ml to 1.0 ~g/ml and exposure times from 48 to 72 hr.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are also consistent with observations made by West et al (1981) to 0.2 gM of m-AMSA for 1 hr, demonstrated distribution patterns with a large variance, similar to the ones we observed at 1 #M m-AMSA. In similar studies, Kao-Shan et al (1984) studied cytogenetic effects of m-AMSA in human lymphocytes, observing potent SCE induction with doses ranging from 0.005 #g/ml to 1.0 ~g/ml and exposure times from 48 to 72 hr.…”
Section: Discussionsupporting
confidence: 82%
“…Huang et al (1983) reported that camptothecin is a very potent inducer of SCEs. West et al (1981) and Kao-Shan et al (1984) observed strong SCE induction by m-AMSA, and Singh and Gupta (1983) also observed very high induction of SCE levels with VM-26. Due to variations in cell line, drug exposure time and dose range, however, it is very difficult to compare relative potency on baseline of these agents.…”
Section: Introductionmentioning
confidence: 96%
“…The similarity between AMSA and ADR as cytotoxic agents has been reported elsewhere [16,20,21]. In an earlier report, we described the cytotoxic effectiveness of ADR to be greatest against FSa cell populations enriched in S-phase [10].…”
Section: Comparison Of Empirical and Theoretical Surviving Fractions supporting
confidence: 74%
“…Moreover, oxygen deprivation also rendered these cells resistant to 5-FU (Fig. 7B), to etoposide (21), and to amsacrine (53). Taken together, the data suggest that the down-regulation of proapoptotic proteins of the Bcl-2 family by oxygen deprivation is not specific to a single cell type and that it is correlated with resistance to a Sixteen hours of oxygen deprivation resulted in the downregulation of Bid, Bax, and Bad in wt MEFs and of Bax and Bad in Bid KO MEFs but did not affect cell viability in either case (Fig.…”
Section: Hif-1-independent Down-regulation Of Bax and Badmentioning
confidence: 99%